Differences Regarding Knowledge of Sexually Transmitted Infections, Sexual Habits, and Behavior Between University Students of Medical and Nonmedical Professions in Serbia - Subotic, Slobodan; Vukomanovic, Vladimir; Djukic, Svetlana; Radevic, Svetlana; Radovanovic, Snezana; Radulovic, Danijela; Boricic, Katarina; Andjelkovic, Jelena; Tosic Pajic, Jelena; Simic Vukomanovic, Ivana (Frontiers in Public Health, 2022)
Introduction: Due to risky sexual behavior, the student population is at risk of developing sexually transmitted infections (STIs). The aim of this study is to assess the knowledge of STIs, sexual habits and behavior among students of medical and non-medical students in Serbia. Methodology: Research is based on the cross-sectional study of the population of university students of four undergraduate institutions in Serbia, two of medical and two of non-medical orientation. Standardized questionnaire, prepared in line with the questionnaire of the European health research - the second wave (European Health Interview Survey - EHIS wave 2), according to defined internationally accepted indicators, was used as a survey instrument. Results: The survey was completed by 1273 randomly selected students who participated in the study. Statistically significant difference was determined for the following parameters: manner of acquiring knowledge on STIs (p < 0.001), number of STI types listed (p < 0.001), STI types (p < 0.001), knowledge about effective vaccine against some STIs (p < 0.001), number of sexual partners (p < 0.001), condom usage (p < 0.001), reason for not using condoms, tested to any STI (p < 0.001), and gynecological/urological examination (p < 0.001). Conclusion: In spite of the fact that students of medical professions have greater knowledge on STIs, both student groups have limited knowledge on possible consequences that risky sexual behavior has for reproductive health. Promotion of knowledge about STIs and awareness of all complications and consequences of these infections certainly affect the reduction of risky behavior.